Digital Technology-Based Marketing For Neglasari Tourist Village Bogor Regency - Yudha, Aditya Prima; Virgantari, Fitria; Setyo Pranowo, Agus; Maharani, Dewi; Awwaqin Putra Hasrin , Adelio; Fadhillah, Restu (CV. Inara, 2024)
Tourist villages are currently becoming an alternative form of tourism by promoting the concept of interaction between nature, culture, and local wisdom. Bogor, as one of the regencies in West Java province, has various interesting tourist destinations to visit, both by local and international tourists. The location of Bogor Regency, surrounded by mountains such as Gunung Gede Pangrango, Gunung Halimun, and Gunung Salak, has various natural tourism potentials. One of the tourist villages in Bogor Regency that offers nature tourism is the Neglasari tourist village. The Neglasari tourist village is traversed by the Cisasa River. The flow of the Cisasa River is utilized by the managers of the Neglasari Tourist Village to offer water tourism packages such as body rafting and river tubing. This river tourism business has been operating since 2021. The Neglasari tourist village is not yet very popular and is not frequently visited by tourists. The average visitation rate is only 4-5 groups of visitors or 20-50 people each month. This is due to the lack of massive promotion and marketing. To increase tourist awareness, digital marketing needs to be carried out with a good concept and done sustainably by utilizing digital marketing platforms such as websites and social media. The community service team from the Faculty of Economics and Business, Pakuan University, conducted training and mentoring programs related to digital marketing for Neglasari Tourism Village. The results of this community service activity include the Neglasari Tourism Village website, social media promotion flyers, content marketing guide modules, and promotional videos for Neglasari Tourism Village.